Presentation skills for technical professionals : achieving excellence - Karten, Naomi (Soft skills for IT professionals., 2010)
Your technical skills and professional expertise are evidence of your ability to accomplish difficult tasks. Strong presentation skills can help you further advance your career. The ability to present articulately to customers, management, peers and others can significantly enhance your credibility, clout, and professional status. Delivering presentations at work or professional events is an unbeatable way to gain a reputation as a valued employee and an expert in your field. If you have ever tried to get out of giving a presentation because of nerves, or if you feel there is room for improvement in your presentation techniques, then Presentation Skills for Technical Professionals is for you. This book gives you invaluable tips on how to make your presentation clear and accessible, how to interact with your audience and how to retain their interest while keeping your anxiety under control. Naomi Karten has used her vast experience -- both positive and negative -- on the front lines of public speaking to provide key advice (and many chuckles!) in this engrossing read for the technical professional.--